LITERASI MEDIA DIGITAL PADA KAMPANYE GREENPEACE ID DI MEDIA SOSIAL INSTAGRAM DALAM PERUBAHAN PERILAKU MASYARAKAT - Pandu Prasetyo (2020)
Greenpeace Id is a non-governmental organization engaged in the environment as a representative of the international organization Greenpeace in Indonesia. Greenpeace Id conducted a campaign on social media Instagram as a means of doing the campaign. The campaign carried out by Greenpeace Id on Instagram must of course be followed by literacy of digital media owned by the community. That is because so that the literacy of digital media owned by the public towards the campaigns carried out by Greenpeace Id on Instagram can be conveyed properly and have an effect on the resulting behavioral changes. This research method uses a qualitative approach. The results of the study can be seen as follows: the four informants namely as followers of Greenpeace Id have understood the literacy capabilities of digital media introduced by Jenkins, et al (2009). The four informants have understood the ability to play, the ability to simulation, the ability to perform performance, the ability of collective intelligence, the ability to judge and the ability to network two of the four informants do not yet have the capability of judgment and networking. Based on the content and posting of Greenpeace's Instagram account is able to provide a response that is a change in behavior that occurs in the community associated with actions to preserve the environment. Accounts like Greenpeace Id are needed in the media to be able to have a positive impact on society.